ANALISIS FAKTOR PENYEBAB KECEMASAN MATEMATIKA PADA MAHASISWA INSTIKI BALI: ANALISIS FAKTOR PENYEBAB KECEMASAN MATEMATIKA PADA MAHASISWA INSTIKI BALI - Krisna, Evi Dwi; Suryati, Ni Kadek (UNIB Press, 2024)
[Analysis Of Factors Causing Mathematics Anxiety In Instiki Bali Students]. The aim of this research is to determine and explain the factors that cause anxiety about learning mathematics at INSTIKI. This research is descriptive with a qualitative approach. The subjects of this research were INSTIKI Bali students. Research data was collected using questionnaires and interviews. The research results show that the anxiety learning mathematics experienced by INSTIKI Bali students is categorized into three groups, there are students with high, medium and low learning outcomes. Factors that cause anxiety about studying mathematics in the high learning outcomes category are intellectual factors including confusion with the material, personality and environmental factors in the form of being stressed during learning due to lack of understanding of explanations but being embarrassed to ask questions, and other factors, namely fear if the grades do not match expectations. The moderate learning outcome category is caused by intellectual factors in the form of lack of ability to learn mathematics, personality factors include lack of self-confidence, and environmental factors include fear of not being able to answer questions that are suddenly given and fear of not being able to solve problems in front of the class. The anxiety factors causing the category of low learning outcomes are intellectual factors in the form of a lack of understanding of mathematics and anxiety during exams, personality factors including of lack of self-confidence, and environmental factors including fear of learning in class and feeling monitored and intimidated by class conditions during learning. Keyword: learning anxiety, mathematics, factor analysis